Characteristics of Emergency Department Patient Visits Referred for Follow-Up Medical Care After Discharge, National Hospital Ambulatory Medicare Care Survey—United States, 2018. (July 2022) - Adekoya, Nelson; Roberts, Henry; Truman, Benedict I.
Objective: To describe characteristics of a nationally representative sample of patient visits that ended with a referral for follow-up medical care after discharge from hospital emergency department (ED) visits. Methods: We used 2018 National Hospital Ambulatory Medical Care Survey data to identify patient characteristics associated with higher rates of visits with referrals for follow-up medical care after ED discharge from nonfederal short-stay and general hospitals throughout the United States. Referral included categories of all disposition variables that indicated referral to a source of care consistent with the patient's clinical condition at ED discharge. Results: Approximately 97 million of 130 million visits (29 700/100 000 US resident population) were referred for follow-up medical care during 2018. Visit referral rates were higher among females (33 100) than among males (26 300/100 000 population); higher among Black patients (61 700) than among White patients (25 600/100 000 population); highest in the South (33 200/100 000 population); and similar rates in Nonmetropolitan (29 900/100 000 population) and Metropolitan Statistical Areas (30 200/100 000 population). Visit referral rates were higher for patients with Medicaid/Children's Health Insurance Program (CHIP) (66 900) than those with Medicare (31 500) or private insurance (14 000/100 000 population). Abnormal clinical findings and injuries were the discharge diagnoses most often referred for follow-up medical care. Conclusion: Higher visit referral rates were observed among female sex, non-Hispanic Black race, Medicaid/CHIP, abnormal clinical findings, and injuries. Future studies might reveal reasons that prompted higher referral rates among various patients' characteristics.